Monitoring of botanical diversity of the state national natural park “Altyn-Emel” (Eurasian Journal of Ecology, 2019)
Abstract. The article provides a brief overview of vegetation stratigraphy, control zones and rare plantsin the Altyn-Emel State National Nature Park. The concept of environmental control, plant diversity,plant diversity, phytocenotic diversity was also interpreted.Objective: Assessment of the current state ofvegetation of the State National Natural Park “Altyn-Emel”. Research methods: Common geobotanical,cartographic. The vegetation cover was studied using traditional methods of field geobotanical research.Field mapping of vegetation was carried out by a combination of the detailed route method and themethod of landscape-ecological profiling using topographic base and satellite images. At the pointsfixed on the ground by the GPS device, a detailed geobotanical description of the main, predominant inarea, plant communities were carried out. Scientific importance is the assessment of the current state ofthe plant cover of the region with unique biodiversity. An assessment of the current state of vegetationcover will make it possible to determine the degree of its disturbance and to identify the main threats tobotanical diversity. The reflection on the maps of key sections of the spatial structure and composition ofvegetation is the most informative way of demonstrating the current state and extent of transformation ofvegetation. Identifying the habitats of wild relatives of cultivated plants and rare plant communities willbe important for the territory of the state national natural park “Altyn-Emel”. The research results servedas the basis for the development of practical measures for the protection of vegetation and biodiversityconservation.Key words: State National Natural Park, monitoring, local, regional, global.